Product Quality Analysis Of Bogor Lapis Cake - Saleha, Saleha; Utami, Nisa Rahmaniyah; Ramadan, Dimas Putra (Universitas Negeri Padang, 2022)
The background of this writing in the culinary world is that there are many forms and kinds of various kinds of food from small to large and from cheap to expensive. For daily needs, there are many activities that are carried out by everyone. The foods available in the market today are indeed quite diverse, in terms of taste, texture, and of course at different prices. The price offered is usually too expensive, and also the benefits contained in it are not accompanied by quality. This research method aims to determine the quality of the product in terms of color, aroma, texture and taste. The method used in this research is descriptive method, with the results saying that the quality of cakes in Lapis Bogor is quite good. Collecting data used in this study using a questionnaire distributed to 100 respondents who are consumers of Lapis Bogor. Based on research on the quality of cakes in Lapis Bogor, the average value of the Color indicator is 3.9, the Aroma indicator is 3.7 while the Texture indicator is 3.7 and the Taste indicator is 4.0. The author concludes that overall it is hoped that the results of this study are good, this research can provide positive input and support from the company and its readers.